Quantifying the impact of microbes on soil structural development and behaviour in wet soils - Helliwell, J.R.; Miller, A.J.; Whalley, W.R.; Mooney, S.J.; Sturrock, Craig (Elsevier, 2014)
There is evidence that microbial populations play an important role in altering soil pore geometry, but a full understanding of how this affects subsequent soil behaviour and function is still unclear. In particular the role of microorganisms in soil structural evolution and its consequence for pore morphological development is lacking. Using a combination of bio-chemical measurements and X-ray Computed Tomography (CT) imaging, a temporal comparison of microscale soil structural development in contrasting soil environments was made. The aim was to quantify the effect of microbial activity in the absence of other features likely to cause soil deformation (e.g. earthworms, roots etc.) on soil structural development in wet soils, defined by changes in the soil porous architecture i.e. pore connectivity, pore shape and pore volume during a 24 week period. Three contrasting soil textures were examined and changes compared between field soil, sterilised soil and a glucose enhanced soil treatment. Our results indicate that soil biota can significantly alter their microhabitat by changing soil pore geometry and connectivity, primarily through localised gaseous release. This demonstrates the ability of microorganisms to modify soil structure, and may help reveal the scope by which the microbial-rich rhizosphere can locally influence water and nutrient delivery to plant roots.